A witch defended by a psychiatrist. (2nd January 2018) - Dhadphale, Manohar
Abstract : Some 40 years ago I was at a loss when I was summoned as an expert witness in an indigenous tribal court to defend a witness accused of witchcraft. The experience shows how the psychiatrist's work requires knowledge of an individual's spiritual framework.